The influence of birth weight, childhood fractures and lifestyle factors on peak bone mass in Norwegian boys and girls between 15-18 years of age. The Tromsø Study, Fit Futures - Christoffersen, Tore (UiT The Arctic University of Norway, 2017)
The papers 1, 3 and 4 of this thesis are not available in Munin. Paper I: Christoffersen, T., Ahmed, L. A., Winther, A., Nilsen, O-A., Furberg, A-S., Grimnes, G., Dennison, E. M., Center, J. R., Eisman, J. A., Emaus, N.: «Fracture incidence rates in Norwegian children, The Tromsø Study, Fit Futures”. Available in Arch Osteoporos 2016, 11:40. Paper III: Christoffersen, T., Ahmed, L. A., Daltveit, A. K., Dennison, E. M., Evensen, E. K., Furberg, A. S., Gracia-Marco, L., Grimnes, G., Nilsen, O. A., Schei, B., Tell, G. S., Vlachopoulous, D., Winther, A., Emaus, N.: “The influence of birth weight and length on bone mineral density and content in adolescence: The Tromsø Study, Fit Futures”. Available in Arch Osteoporos 2017, 12(1):54. Paper IV: Christoffersen, T., Emaus, N., Dennison, E. M., Furberg, A-S., Gracia-Marco, L., Grimnes, G., Nilsen, O-A., Vlachopoulos, D., Winther, A., Ahmed, L. A.: “The association between childhood fractures and adolescence bone outcomes: a population based study, The Tromsø Study, Fit Futures”. (Manuscript). The basis of bone strength is created during early development and growth, before the achievement and consolidation of a peak bone mass (PBM) in the second or early third decade of life. In order to optimize PBM, we need to identify modifiable predictors that influence bone mass accrual during growth and the vulnerable period of adolescence. The main aim of this thesis was to investigate the influence of birth parameters, childhood fractures and lifestyle factors on the accrual of bone mass levels among Norwegian adolescents. The Tromsø Study, Fit Futures is an expansion of the population-based Tromsø Study. In 2010/2011 we invited all first-year upper-secondary school students in Tromsø and surrounding municipalities to a health survey. In total 1038 adolescents attended, 508 girls and 530 boys, providing an attendance rate of 93%. We measured hip and total body bone mineral content (BMC) (g), bone mineral density (BMD) (g/cm²) by Dual-energy X-ray absorptiometry (DXA). Weight ...